"We're a walking picket sign": Management of a Stigmatized Religious Identity. Issue 2 (1st February 2019) - Pimentel, Alexandra; Melander, Lisa
ABSTRACT: This study analyzes qualitative data from interviews with 18 members of the Westboro Baptist Church (WBC) focusing on the group's religious identity and relationships with "mainstream" society. Two primary themes emerged. First, the WBC religious identity appears to hinge on external conflict with society which is promoted by their core religious ideology and negotiated through various stigma management strategies. Second, members of the church enjoy strong internal group cohesion promoted by their religious ideology and symbolic boundaries that separate them from outside institutions. This study therefore suggests stigmatization offers social benefits to members of the WBC in addition to social consequences.